Mitochondrial dysfunction as a possible trigger of neuroinflammation at post-traumatic stress disorder (PTSD) - Dmytriv, Tetiana R.; Tsiumpala, Sviatoslav A.; Semchyshyn, Halyna M.; Storey, Kenneth B.; Lushchak, Volodymyr I. (Frontiers in Physiology, 2023)
Post-traumatic stress disorder (PTSD) is a neuropsychiatric disorder that occurs in approximately 15% of people as a result of some traumatic events. The main symptoms are re-experiencing and avoidance of everything related to this event and hyperarousal. The main component of the pathophysiology of PTSD is an imbalance in the functioning of the hypothalamic-pituitaryadrenal axis (HPA) and development of neuroinflammation. In parallel with this, mitochondrial dysfunction is observed, as in many other diseases. In this review, we focus on the question how mitochondria may be involved in the development of neuroinflammation and its maintaining at PTSD. First, we describe the differences in the operation of the neuro-endocrine system during stress versus PTSD. We then show changes in the activity/expression of mitochondrial proteins in PTSD and how they can affect the levels of hormones involved in PTSD development, as well as how mitochondrial damage/pathogen-associated molecule patterns (DAMPs/PAMPs) trigger development of inflammation. In addition, we examine the possibility of treating PTSD-related inflammation using mitochondria as a target.